A Narrative Approach to Exploring Life Changes Among Middle-Aged Women: A Qualitative Study - Nasrin Rezaee; Mahnaz Ghaljeh (Iranian Journal of Nursing and Midwifery Research)
Background: Middle age serves as a crucial transitional phase between youth and old age in women’s health, making it a critical period for women. Accordingly, this study aimed to explore the experiences of life changes among middle-aged women. Materials and Methods: This study was conducted using qualitative content analysis from September to December 2022 in Zahedan. The participants included 10 middle-aged women selected via purposive sampling. Data were collected through individual face-to-face interviews, and all interviews were subsequently transcribed and analyzed. Categories representing the beginning, middle, and end of the narratives were extracted. First, thematic similarities were identified, leading to the emergence of subcategories. Then, the related subcategories were reviewed and placed into the same category. Results: At the beginning of the narratives, the identified subcategories included perception of middle age, gaining experience, and behavior change. In the middle of the narratives, understanding the developmental stages and gaining experience in managing life were extracted as the subcategories. At the end of the narratives, maturity was identified as the main category. Conclusions: The findings from this study revealed that development occurs through the accumulation of experience. Although this study did not explore development in contextual terms, addressing and identifying the challenges of middle age in their context may facilitate quicker development. Furthermore, recognizing and investigating physical problems associated with middle age could lead to more timely treatment.